KuQuinones: a new class of quinoid compounds as photoactive species on ITO. Issue 3 (23rd December 2015) - Sabuzi, F.; Armuzza, V.; Conte, V.; Floris, B.; Venanzi, M.; Galloni, P.; Gatto, E.
Abstract : KuQuinones deposited on ITO surface by Langmuir–Blodgett technique acted as photosensitizers, giving interesting results due to their pentacyclic, highly conjugated structure, and a very low reduction potential. Abstract : KuQuinones constitute a new class of quinoid compounds, characterized by a broad absorption spectrum in the visible region, mainly due to their pentacyclic, highly conjugated structure, and a very low reduction potential. These properties make them promising candidates as sensitive material in photoelectrochemical devices. To this purpose, photocurrent generation measurements have been performed, in presence of an electron donor species in solution, using two different derivatives, 1-(9-hydroxynonyl)KuQuinone (KuQ(CH2 )9 OH) and 1-methylKuQuinone (KuQCH3 ), as photoactive species on indium-tin oxide surface. Electrodes have been functionalized by Langmuir–Blodgett technique, which allowed to easily prepare homogeneous mono- and multilayers of such molecules. Promising results in terms of Incident Photon to Current Efficiency values (IPCE%) and internal quantum efficiency ( Φ %) have been achieved. Furthermore, the significance of the organization of the thin film obtained for the efficiency of the electron transfer process has been evidenced.